Seabuckthorn cultivation and research in North Ostrobothnia, Finland [Elektroninen aineisto] - Prokkola, Soile (cn, 2002)
The cultivation area of sea buckthorn has increased rapidly during recent years in Finland. In 2000 sea buckthorn was cultivated over a total area of 116 ha. In the North Ostrobothnia region the cultivated area was 24.5 ha, but only 4.1 ha yielded berries, because most of the area was newly established The problems limiting cultivation of sea buckthorn are the lack of cultivars which are reliable under cultivation and the difficulty of harvesting. At the North Ostrobothnia Research Station of MTT (Agrifood Research Finland), sea buckthorn research has concentrated on variety trials, breeding and mechanization of harvesting.
Keywords: Pu; tyrni; lajikkeet; sadonkorjuu